EP599 Does intraperitoneal chemotherapy represent a strategy for treatment of malignant ascites in recurrent endometrial cancer patients? Three cases-report and a literature review. (1st November 2019) - Perniola, G; Santangelo, G; Palaia, I; Musella, A; Di Pinto, A; Derme, M; Romito, A; Caruso, G; Di Donato, V; Tomao, F; Muzii, L; Benedetti Panici, P
Abstract : Introduction/Background: Endometrial cancer is generally associated with a good prognosis, due to an early diagnosis in stage I and II, 75% and 13% respectively. For advanced-stage disease, the recurrence rate is high and the site of the relapse is heterogeneous with localized or spread peritoneal disease. The treatment strategy is based on site of relapse. For non-localized relapse the chances are limited with a poor prognosis. Methodology: We reported our experience of three cases with peritoneal spread recurrences, in endometrial cancer patients with advanced stage diagnosis. Results: The patients had been underwent to multiple lines of chemotherapy including rechallenging with platinum regimens, pegilated liposomal doxorubicin and taxane, with a progression of disease. These patients came at our Department for abdominal distension and breathing difficulty, CA 125 increased and radiology find (CT scan or US scan) of ascites. In these cases, after paracentesis and a single administration of intraperitoneal chemotherapy based on carboplatin (AUC5) were showed quality of life improvement, reduction of fatigue, improved breathing and reduction of anorexia. No complications occurred. Conclusion: Although only few cases have been reported, the exceptional results and the absence of side effects observed in these cases, strongly warrant future trials to investigate the role that intraperitoneal chemotherapy can have both as palliative treatment of refractory ascites and as salvage therapy in advanced endometrial cancer. Disclosure: All authors declare that they have no conflict of interest and nothing to disclose.